(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Educating the young generation, providing them with the education and upbringing process based on the requirements of the times, requires today’s pedagogues not only to be experts in their fields, but also to acquire innovative and psychological knowledge at the same time. In the twenty-first century, which is the age of information, it is impossible to imagine the educational process without modern technology and psychological knowledge